PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS BRAIN BASED LEARNING KELAS XI SMA NEGERI 20 MERANGIN - Jarmiah; Ferinaldi; sukur (Hiradika | Hira Institute, 2026)
The research was motivated by the incomplete LKPD of students at SMA Negeri 20 Merangin, the lack of student activity in mathematics learning and student learning outcomes that were still below the KKTP. The purpose of the research is to produce valid, practical and effective Brain Based Learning LKPD. The type of research is Research & Development (R&D). The 4D development model consists of the Define, Design, Development and Disseminate stages. The development of learning products has passed the validation stage of material experts obtaining an average score of 4.44 in the very valid criteria, validation of language experts obtaining an average score of 5 in the very valid criteria, validation of media experts obtaining an average score of 4.95 in the very valid criteria, and validation of practitioner experts obtaining a score of 4.88 in the very valid criteria. The overall validation results obtained an average of 4.81 in the very valid criteria. The practicality of Brain Based Learning LKPD obtained an average score of 83.51% in the very practical criteria. The effectiveness of Brain-Based Learning LKPD in terms of learning activities obtained an average score of 84.25% in the very active criteria. And student learning outcomes obtained completeness of 81.81% in the effective criteria. Based on the results of research and development, it shows that the Brain-Based Learning LKPD developed have been declared very valid, practical and effective